THE RESULTS OF RESEARCH TO IMPROVE THE RELIABILITY OF THE SYSTEM OF AUTOMATIC CONTROL MODES, TRACTION CONTROL SYSTEM OF AUTOMATIC CONTROL MODES OF TRACTION AND REGENERATIVE-RHEOSTATIC BRAKING ON TRAINS ER2T - Visyn, M. H.; Vlasenko, B. T.; Sokolov, S. O. (Science and Transport Progress, 2007)
In work recuperative and rheostatic braking an electric train AYR2T in a range from 120 up to 15 km/h, are given the recommendation on driving on driving trains is investigated.